2010
DOI: 10.1126/science.1196914
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative Analysis of the Caenorhabditis elegans Genome by the modENCODE Project

Abstract: We systematically generated large-scale data sets to improve genome annotation for the nematode Caenorhabditis elegans, a key model organism. These data sets include transcriptome profiling across a developmental time course, genome-wide identification of transcription factor–binding sites, and maps of chromatin organization. From this, we created more complete and accurate gene models, including alternative splice forms and candidate noncoding RNAs. We constructed hierarchical networks of transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
1,029
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 947 publications
(1,097 citation statements)
references
References 76 publications
53
1,029
2
3
Order By: Relevance
“…These factors may include transcription factors, DVE‐1, CEH‐23, and CEP‐1, which regulate longevity in response to inhibition of mitochondrial components (Durieux et al ., 2011; Walter et al ., 2011; Baruah et al ., 2014), because nhr‐57 is induced by impaired mitochondrial functions (Lee et al ., 2010). In addition, transcription factors, such as ELT‐3, EOR‐1, BLMP‐1, ALR‐1, PHA‐4, PQM‐1, SKN‐1, MDL‐1, and PES‐1, bind to the promoter region of nhr‐57 , based on modENCODE data analysis (Gerstein et al ., 2010; Van Nostrand & Kim, 2013). It would be interesting to determine whether these transcription factors cooperate with HIF‐1 to regulate nhr‐57 induction and longevity.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may include transcription factors, DVE‐1, CEH‐23, and CEP‐1, which regulate longevity in response to inhibition of mitochondrial components (Durieux et al ., 2011; Walter et al ., 2011; Baruah et al ., 2014), because nhr‐57 is induced by impaired mitochondrial functions (Lee et al ., 2010). In addition, transcription factors, such as ELT‐3, EOR‐1, BLMP‐1, ALR‐1, PHA‐4, PQM‐1, SKN‐1, MDL‐1, and PES‐1, bind to the promoter region of nhr‐57 , based on modENCODE data analysis (Gerstein et al ., 2010; Van Nostrand & Kim, 2013). It would be interesting to determine whether these transcription factors cooperate with HIF‐1 to regulate nhr‐57 induction and longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide chromatin immunoprecipitation (ChIP) experiments in diverse metazoans have shown that many transcription factors bind thousands of highly overlapping loci in undifferentiated cells (Boyer et al 2005;Moorman et al 2006;Zeitlinger et al 2007;Chen et al 2008;Li et al 2008;Marson et al 2008;Bradley et al 2010;Gerstein et al 2010;Roy et al 2010;He et al 2011;Negre et al 2011). Many known enhancers of gene expression are bound by multiple transcription factors, suggesting that highly overlapping transcription factor binding may imply cis-regulatory potential.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…A combination of ChIP sequencing or ChIP-PCR and the TF-induced differential gene expression is needed to reveal the functional network and its regulatory effects. This combination has been used to discover specific functional regulatory networks in animal development, using cell cultures representing different developmental stages where specific sets of TFs are induced (Yu and Gerstein, 2006;Farnham, 2009;Bhardwaj et al, 2010;Gerstein et al, 2010;Roy et al, 2010;Cheng et al, 2011). These TF regulatory networks are arranged in well-organized hierarchies.…”
Section: Introductionmentioning
confidence: 99%
“…For tree species that are amenable to genetic transformation, methods are technically demanding and slow, requiring 12 to 18 months of tissue culture (Merkle and Dean, 2000). To reveal a functional hGRN for wood formation, an efficient transgenic system, such as those developed for the cell cultures of yeast (Saccharomyces cerevisiae) and animals (Horak et al, 2002;Yu and Gerstein, 2006;Gerstein et al, 2010;Cheng et al, 2011;Niu et al, 2011), is needed where immediate transcriptome responses to TF perturbation can be induced, characterized, and quantified.…”
Section: Introductionmentioning
confidence: 99%